Role of Genetic Testing in Patients undergoing Percutaneous Coronary Intervention - Moon, Jae Youn (Expert Rev Clin Pharmacol, 2017)
INTRODUCTION: Variability in individual response profiles to antiplatelet therapy, in particular clopidogrel, is a well-established phenomenon. Genetic variations of the cytochrome P450 (CYP) 2C19 enzyme, a key determinant in clopidogrel metabolism, have been associated with clopidogrel response profiles. Moreover, the presence of a CYP2C19 loss-of-function allele is associated with an increased risk of atherothrombotic events among clopidogrel-treated patients undergoing percutaneous coronary interventions (PCI), prompting studies evaluating the use of genetic tests to identify patients who may be potential candidates for alternative platelet P2Y(12) receptor inhibiting therapies (prasugrel or ticagrelor). AREAS COVERED: The present manuscript provides an overview of genetic factors associated with response profiles to platelet P2Y(12) receptor inhibitors and their clinical implications, as well as the most recent developments and future considerations on the role of genetic testing in patients undergoing PCI. EXPERT COMMENTARY: The availability of more user-friendly genetic tests has contributed towards the development of many ongoing clinical trials and personalized medicine programs for patients undergoing PCI. Results of pilot investigations have shown promising results, which however need to be confirmed in larger-scale studies to support the routine use of genetic testing as a strategy to personalize antiplatelet therapy and improve clinical outcomes.